First-time report on compound isolation from two Colocasia species: vegetable-derived bioactive metabolites and their medicinal potential - Alam, Safaet; Richi, Fahmida Tasnim; Emon, Nazim Uddin; Chowdhury, Abu Asad; Hasan, Choudhury Mahmood; Haque, Mohammad Rashedul (Frontiers in Pharmacology, 2024)
Background: Colocasia affinis Schott and Colocasia gigantea Hook.f. are two commonly found vegetable species from Colocasia genus found mainly in the Asian region. Objectives: The objective of this study was to isolate bioactive phytochemicals from C affinis and C. gigantea and elucidate their structure employing NMR technique followed by bioactivity evaluation. Methodology: Column chromatography was utilized to isolate phytochemicals followed by NMR analysis for characterization. In-vivo analgesic test was performed through acetic acid-induced writhing test, anti-inflammatory through formalin-induced licking test and antidiarrheal through castor-oil induced diarrhea model. In-vitro antimicrobial test was executed through disc-diffusion method. Computer-aided simulation was also implemented to validate wet lab results. Results: Six compounds from C. affinis and C. gigantea were isolated and characterized from the dichloromethane (DCM) soluble fractions of the methanolic extracts of these two species. Three of the compounds were from C. gigantea and proposed as Penduletin (C1), a mixture of α-amyrin (C2a) and β-amyrin (C2b), and monoglyceride of stearic acid (C3) while rest of the three compounds were from C. affinis and proposed as Penduletin (C4) (which was isolated from C. gigantea also), 7,8- (3'',3''-dimethyl-pyrano)-4′-hydroxy flavonol (C5), and lastly a mixture of 7,8- (3'',3''-dimethyl-pyrano)-4′-hydroxy flavonol (C5) and 4',7,8- trihydroxy flavonol (C6). These compounds showed promising zone of inhibitions against gram-positive, gram-negative bacteria and fungi. In the antidiarrheal test, C5 demonstrated the highest reduction in castor oil-induced diarrhea (44.44%) at 20 mg/kg dose compared to loperamide’s 77.78% reduction. However, analgesic assessment showed noteworthy inhibition of acetic acid-induced writhing by C1/C4, and C2 (56.52%) at 20 mg/kg dose compared to the 76.09% by diclofenac sodium while C2 showed pronounced anti-inflammatory action by 68.15% and 52.06% reduction respectively in early and later phase compared to the ibuprofen’s outcomes of 73.54% and 74.68%. Responsible targets such as dihydrofolate reductase (DHFR) for anti-microbial, kappa opioid receptor (KOR) for antidiarrheal, and cyclooxygenase 2 (COX-2) for anti-inflammatory and analgesic activities showed noteworthy binding affinity with isolated compounds while ADME/T studies displayed these phytochemicals’ drug-likeliness profiles. Conclusion: Finally, to the best of our knowledge this is the first-time report on compound isolation from these plants which demands further extensive research.